Manufacturing method of lithium manganese iron phosphate, positive electrode material and lithium ion battery

A solid-phase synthesis method for lithium manganese iron phosphate addresses performance and cost issues by producing a material with high tap density and long cycle life, enhancing lithium ion battery performance.

JP7602031B2Active Publication Date: 2024-12-17PHYLION BATTERY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023524514
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-04-01
Filing Date
2022-10-31
Publication Date
2024-12-17
Estimated Expiration
2042-10-31

AI Technical Summary

Technical Problem

Existing methods for synthesizing lithium manganese iron phosphate materials face challenges such as low performance, high cost, environmental pollution, and poor cycle life, making them unsuitable as a standalone positive electrode material for lithium ion batteries.

Method used

A new solid-phase synthesis method involving the thermal decomposition of manganese and iron sources to form manganese iron oxide, followed by sintering with lithium and phosphorus sources to produce lithium manganese iron phosphate, enhancing tap density, compaction density, and reducing specific surface area.

Benefits of technology

The method results in lithium manganese iron phosphate with high tap density, long cycle life, low cost, and improved energy density, suitable for lithium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602031000003
    Figure 0007602031000003
  • Figure 0007602031000004
    Figure 0007602031000004
  • Figure 0007602031000005
    Figure 0007602031000005
Patent Text Reader

Abstract

In the present invention, a manganese source and / or an iron source are solid-phase mixed to obtain a first mixture in step S1, and the first mixture is solid-phase sintered at 300 to 1200° C. to obtain manganese iron oxide (Mn x Fe 1-x-y ) m O n and a step S2 of obtaining the manganese iron oxide (Mn x Fe 1-x-y ) m O n Step S3 of solid-phase mixing the lithium source, the phosphorus source, and, if necessary, the manganese source and / or the iron source to obtain a second mixture; and step S4 of solid-phase sintering the second mixture at 350 to 900° C. to obtain lithium manganese iron phosphate LiMn x Fe 1-x-y PO 4 where 0≦x≦1 and 0≦y≦1. According to the method of the present invention, a lithium manganese iron phosphate material having a high tap density, a long cycle life, a low cost, and high cost performance can be produced.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of lithium ion battery manufacturing, and more particularly to a method for manufacturing lithium manganese iron phosphate, and a positive electrode material and a lithium ion battery manufactured thereby. [Background technology]

[0002] The positive electrode materials commonly used in lithium-ion batteries are shown in Table 1 below. JPEG0007602031000001.jpg60170

[0003] Ternary positive electrode materials (lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminate) are generally used in the field of power batteries instead of lithium cobalt oxide. Ternary positive electrode materials have low-temperature discharge capability, normal temperature cycle, high temperature cycle, and the highest energy density. As can be seen from the table, as the nickel content increases, the gram capacity of the material gradually increases, but the thermal decomposition temperature of the material decreases, which reduces the safety of lithium-ion batteries with ternary positive electrode material systems. On the other hand, low-nickel ternaries such as 111 ternaries have a high cobalt content, so the material price is high, and when the nickel content (nickel content in the total of nickel, cobalt, manganese or aluminum) exceeds 70%, for example, in the case of high-nickel 811 ternary materials, an oxygen atmosphere is required during the sintering process, so the material price is also high. In addition, cobalt and nickel are scarce on the earth, so they are expensive. Therefore, ternary materials are suitable for medium-sized and high-end cars with long driving ranges.

[0004] The synthesis of positive electrode ternary materials requires the involvement of oxygen. Generally, under low- and medium-nickel conditions, manufacturers sinter under air conditions, but under high-nickel conditions (nickel>0.7), sintering is required under oxygen atmosphere. In addition, high-nickel is relatively sensitive to air humidity, and is prone to absorbing moisture and forming lithium carbonate on the surface of the material. Therefore, the packaging and coating of battery materials have high requirements for humidity. As a result, the labor costs required for high-nickel are higher than those for medium-nickel. In recent years, there have been many safety accidents involving long-distance electric vehicles equipped with high-nickel ternary systems, and the industry's enthusiasm for high-nickel ternary systems has declined. At present, the pursuit of high-nickel is gradually shifting to the use of medium-nickel ternary systems. With the progress of research and development and the market drive to reduce costs, the application of low-cobalt / cobalt-free ternary systems is accelerating. At present, the cobalt content has gradually decreased to 0.05 and even 0.03. However, cobalt and nickel occur together in natural minerals, and pure nickel also contains 3-5% cobalt, so there is no need to incur the costs of removing the cobalt from high-nickel ternary systems.

[0005] The safety performance of lithium manganese oxide materials is obviously higher than that of ternary positive electrode materials, and they have excellent low-temperature and rate performance and are inexpensive, but their gram capacity is low (~110mAh / g) and their cycle life, especially high-temperature cycle life, is poor. Therefore, it is difficult to use lithium manganese oxide alone as a positive electrode material.

[0006] Lithium-rich manganese-based materials are representative of new positive electrode materials. When charged to 4.8 V, the specific capacity can reach more than 250 mAh / g, but the cycle is unstable. At present, mature commercialized electrolytes are mainly 4.2 V systems, which are electrolytes that combine single crystal ternary systems with 4.3 to 4.4 V systems. Since 5 V high voltage system electrolytes are not yet mature, lithium-rich manganese-based materials are not widely used, and only a small amount is used in doping lithium manganese oxide to delay the problem of fast initial decay of lithium manganese oxide cycles.

[0007] Lithium iron phosphate is a commonly used cathode material for lithium-ion batteries. It has a long cycle life and excellent safety, but its electrical conductivity is low, so in commercial applications, its rate performance is compensated for by its small particle size. Nevertheless, lithium iron phosphate is difficult to discharge at low temperatures, and its discharge capacity is concentrated in the platform area, making it difficult to regulate the state of charge and voltage, resulting in a poor user experience. The compressed density of lithium iron phosphate is low, only 2.4-2.5 g / cm. 3 whereas lithium manganate has a density of 3.1 g / cm 3 and the ternary positive electrode reached 3.4 / cm 3 , and the lithium iron voltage is only 3.2V. Therefore, the volumetric energy density of lithium iron phosphate is very low. Therefore, LiMnPO4, LiCoPO4, LiNiPO4, LiMnSiO4, LiFeSiO4, LiCoSiO4, LiNiPSiO4 are materials expected to replace lithium iron phosphate. Compared with silicate systems, the commercialization of phosphate systems is more mature. Among the four elements of manganese, cobalt, nickel, and iron, cobalt and nickel are the most expensive, and manganese and iron are the cheapest. However, lithium manganese phosphate has extremely low electrical conductivity, lower than lithium iron phosphate. Eclectic, manganese-doped lithium iron phosphate and iron-doped lithium manganese phosphate both use the high potential platform of manganese and the structural stability of iron to synthesize lithium manganese iron phosphate, and lithium manganese iron phosphate combines the properties of lithium manganese phosphate and lithium iron phosphate by doping manganese or iron. These three kinds of substances are combined into one material with one chemical formula LiMn x Fe 1-xIt may be expressed as PO4. Although lithium manganese iron phosphate has already matured commercially, its conductivity is lower than that of lithium iron phosphate, and its low-temperature discharge capability is also weak, so it is not currently used alone as a positive electrode material. The platform voltage of lithium manganese iron phosphate is as high as 4.1V, the medium voltage reaches 3.9V, and the gram capacity and cycle life are consistent with lithium iron phosphate. In the 4.2-4.3V system, its safety performance is extremely high, and it is mixed into ternary materials to improve the safety performance of overcharging and needle puncture.

[0008] At present, the synthesis methods of lithium iron phosphate are classified into solid-phase and liquid-phase methods. The liquid-phase method mainly uses iron (II) sulfate heptahydrate, phosphoric acid, and lithium hydroxide to produce lithium iron phosphate, lithium sulfate, and water through hydrothermal reaction. However, the equipment is expensive, and generally three times the amount of lithium hydroxide is used as a precipitant, that is, 200% of lithium hydroxide needs to be consumed, which increases the cost. The solid-phase method is classified into iron (II) oxalate, iron oxide (red), and iron (III) orthophosphate methods. The iron (II) oxalate method generates a large amount of carbon dioxide gas during the reaction process, which results in large carbon loss, fluctuating carbon content, poor product consistency, low tap density of the product, and releases ammonia gas to pollute the environment. The iron oxide (red) method is relatively low in cost and the density of the synthesized lithium iron phosphate is relatively large, but the capacity is low and ammonia gas is released to pollute the environment. The iron orthophosphate (III) method is the mainstream production process because it does not generate ammonia gas, is environmentally friendly, and has a large production volume. There are two methods for synthesizing iron orthophosphate (III): the iron sulfate (II) method and the iron powder-phosphoric acid method. Both of these methods require the use of phosphoric acid and hydrogen peroxide, which requires corrosion prevention in the equipment, resulting in high costs and a large burden on environmental protection. At present, the synthesis methods of lithium manganese iron phosphate are mainly classified into solid-phase method and co-precipitation method. The solid-phase method adopts sintering of manganese source, iron source, phosphorus source, and lithium source, and the process is the simplest, but the performance of the synthesized material is the worst, so the co-precipitation method is the mainstream. The co-precipitation method is to co-precipitate the manganese source, iron source, and complexing agent to generate a precursor, and the precursor reacts with the phosphorus source and lithium source in the solid or liquid phase to generate lithium manganese iron phosphate (for example, Chinese invention patent CN105047922A).

[0009] LiMn x Fe 1-x Although PO4 is lithium iron phosphate when x=0 or lithium manganese iron phosphate when x≠0, the synthesis of materials can be clearly classified into solid-phase and liquid-phase methods. The solid-phase method has a simple process but the performance of the synthesized material is the worst. The liquid-phase method synthesizes good performance of the synthesized material, but the cost is high and the burden on environmental protection is large due to the corrosion prevention requirements of the equipment. Therefore, LiMn x Fe 1-x New design processes for synthesizing PO4 materials are needed. Summary of the Invention

[0010] The present invention provides a method for producing lithium manganese iron phosphate, which can produce a lithium manganese iron phosphate material with high tap density, long cycle life, low cost, and high cost performance. The present invention further provides a cathode material and a lithium ion battery produced from the material.

[0011] The method for producing lithium manganese iron phosphate provided by the present invention includes the steps of: A step S1 of mixing a manganese source and / or an iron source in a solid phase to obtain a first mixture; The first mixture is solid-phase sintered at 300 to 1200° C. to obtain manganese iron oxide (Mn x Fe 1-x-y ) m O n Step S2 to obtain The manganese iron oxide (Mn x Fe 1-x-y ) m O n a step S3 of solid-phase mixing the lithium source, the phosphorus source, and optionally the manganese source and / or the iron source to obtain a second mixture; The second mixture is solid-phase sintered at 350 to 900° C. to obtain lithium manganese iron phosphate LiMn x Fe 1-x-y A step S4 of obtaining PO4; where 0≦x≦1 and 0≦y≦1.

[0012] In the prior art, the solid-state method for lithium manganese iron phosphate involves mixing a manganese source, an iron source, a phosphorus source, and a lithium source, followed by sintering. This is a simple process, but the performance of the synthesized material is the worst. Based on this, the present invention provides a new manufacturing method. First, the manganese source and the iron source are mixed and solid-state sintered to thermally decompose the manganese source and the iron source to produce manganese iron oxide (Mn x Fe 1-x-y ) m O n Next, manganese iron oxide (Mn x Fe 1-x-y ) m O n After mixing with a lithium source and a phosphorus source, the second solid-state sintering is performed to obtain lithium manganese iron phosphate LiMn x Fe 1-x-y PO 4-zThis manufacturing method is similarly simple, and the obtained lithium manganese iron phosphate is inexpensive, has the characteristics of high tap density and compressed density, high energy density, small specific surface area, small self-discharge, and long cycle life, which are obviously superior to lithium manganese iron phosphate produced by conventional solid-phase and liquid-phase methods. In the method of the present invention, the first thing synthesized is manganese iron oxide, which is the precursor of lithium manganese iron phosphate, and the true density of manganese iron oxide is higher than that of iron oxide and lower than that of manganese oxide, and the true density of iron oxide is higher than that of iron salts, such as iron (II) sulfate. Furthermore, when synthesizing lithium manganese iron phosphate, the conventional solid-phase method uses an iron source, a manganese source, a lithium source, and a phosphorus source to synthesize lithium manganese iron phosphate, and because of the presence of a low-density iron source, the synthesized lithium manganese iron phosphate material has a low tap density and a large specific surface area, and the prepared electrode sheet has a low compressed density, low energy density, large self-discharge, and a slightly poor cycle. In the conventional liquid phase method, iron manganese carbonate or iron manganese hydroxide is co-precipitated, and the morphology is porous and the density is low. The iron manganese source, lithium source, and phosphorus source co-precipitated later are used to synthesize the lithium manganese iron phosphate material, which is similarly characterized by low tap density, large specific surface area, low compressed density of the electrode sheet, low energy density, large self-discharge, and rather poor cycle life. In addition, the manganese iron oxide, which is the precursor of the lithium manganese iron phosphate synthesized by the method of the present invention, is in the form of a primary single crystal with large particles and has a high true density, so that the finally synthesized lithium manganese iron phosphate material has a high tap density, a high compressed density of the electrode sheet, a high energy density of the battery, a small specific surface area of ​​the material, a small self-discharge, and a long cycle life.

[0013] The manganese source may be any of various manganese compounds commonly used in the art, and the present invention is not limited thereto. The manganese source may or may not contain crystal water. Preferably, the manganese source is one or more of manganese sulfate, manganese carbonate, manganese acetate, manganese phosphate, manganese nitrate, manganese oxalate, and manganese citrate.

[0014] The iron source may be any of various iron compounds commonly used in the art, and the present invention is not limited thereto. The iron source may or may not contain crystal water. Preferably, the iron source is one or more of iron sulfate (II), iron carbonate (II), iron acetate (II), iron phosphate (II), iron nitrate (II), iron oxalate (II), iron citrate (II), iron sulfate (III), iron carbonate (III), iron acetate (III), iron phosphate (III), iron nitrate (III), iron oxalate (III), and iron citrate (III).

[0015] The lithium source may be any of various lithium compounds commonly used in the art, and the present invention is not limited thereto.Preferably, the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium phosphate, lithium oxalate, lithium acetate, lithium sulfate, lithium nitrate, and lithium chloride.

[0016] The phosphorus source can be any phosphorus-containing compound commonly used in the art, and the present invention is not limited thereto.Preferably, the phosphorus source is one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium tripolyphosphate, phosphoric acid, calcium phosphate, phosphate ester, lithium dihydrogen phosphate, iron(III) phosphate, lithium phosphate, lithium dihydrogen phosphate, and manganese phosphate.

[0017] In step S1 of the present invention, a manganese source or an iron source may be used alone. When a manganese source is used alone, lithium manganese phosphate can be produced, and lithium iron manganese phosphate (iron source is replenished in step S3) can also be produced. Similarly, when an iron source is used alone, lithium iron phosphate can be produced, and lithium iron manganese phosphate (manganese source is replenished in step S3) can also be produced. Here, the iron source and / or manganese source replenished in step S3 are preferably iron oxide and / or manganese oxide.

[0018] In the present invention, the amounts of the manganese source, iron source, lithium source, and phosphorus source added are mainly manganese iron oxide (Mn x Fe 1-x-y ) m O n and lithium iron manganese phosphate LiMn x Fe 1-x-y It is determined according to the stoichiometric ratio of the PO4 synthesis reaction formula.

[0019] Furthermore, in steps S1 and S3, one or more of a carbon source, an M source, and an N source are further added during solid-state mixing. After the solid-state sintering in steps S2 and S4, manganese iron oxide (Mn x Fe 1-x-y M y ) m O n N z / C and lithium manganese iron phosphate LiMn x Fe 1-x-y M y PO 4-z N z / C, where the M source is a doping cation source and the N source is a doping anion source, 0≦x≦1, 0≦y≦1, 0≦z≦0.1, 1:3.5≦m:(n+z)≦1:1, such as FeO, Fe2O3, Fe3O4.

[0020] In the present invention, the addition of a carbon source can form a carbon-coated lithium manganese iron phosphate material. The carbon source can be one or more of an organic carbon source or an inorganic carbon source. Preferably, the carbon source is one or more of sucrose, glucose, fructose, citric acid, phenolic resin, polyvinyl alcohol, polyethylene glycol, starch, carbon black, acetylene black, graphite, graphene, and conductive carbon tubes.

[0021] In the present invention, the addition of the M source can provide a cation-doped lithium manganese iron phosphate material, where the M source can be one or more cation sources, preferably comprising one or more of the following elements: aluminum, magnesium, nickel, cobalt, titanium, copper, calcium, niobium, chromium, zinc, lanthanum, antimony, tellurium, strontium, tungsten, indium, yttrium, etc.

[0022] In the present invention, the addition of a N source can provide an anion-doped lithium manganese iron phosphate material, where the N source can be one anion source or multiple anion sources. Preferably, the anion source includes one or more of the elements such as fluorine, sulfur, etc.

[0023] The manufacturing method of the present invention can provide materials such as lithium manganese iron phosphate materials having an olivine structure, layered lithium polybasic acids, spinel-type lithium manganese oxides, and layered manganese-rich lithium base materials.

[0024] The positive electrode material provided by the present invention is obtained by mixing one or more of the above-mentioned olivine-structured lithium manganese iron phosphate material, layered lithium polybasic acid, spinel-type lithium manganate, and layered manganese-rich lithium base.

[0025] The lithium ion battery provided by the present invention includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator, and the positive electrode sheet is made of the above positive electrode material.

[0026] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention provides a new solid-phase synthesis method for lithium manganese iron phosphate by improving the synthesis process. The lithium manganese iron phosphate material synthesized by this method has high tap density, high pressed density and small specific surface area, and the lithium ion battery produced by it has the characteristics of high energy density, small self-discharge and long cycle life. 2. The lithium manganese iron phosphate material synthesized in the present invention has the advantages of being inexpensive and having high cost performance. [Brief description of the drawings]

[0027] [Figure 1] 1 is an XRD pattern of (Mn0.9Fe0.1)2O3 in Example 1 of the present invention. [Diagram 2] 1 is a SEM image of (Mn0.9Fe0.1)2O3 in Example 1 of the present invention. [Diagram 3] 1 is a SEM image of LiMn0.9Fe0.1PO4 in Example 1 of the present invention. [Figure 4] 1 is a SEM image of LiMn0.9Fe0.1PO4 in Example 2 of the present invention. [Diagram 5] FIG. 2 is a test diagram of cycle performance of cylindrical full batteries manufactured in Example 3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this invention belongs. The terms used herein in describing the present invention are only for describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the associated items.

[0029] The present invention will now be further described with reference to the drawings and specific examples in order to enable those skilled in the art to better understand and practice the present invention, but the following examples are not intended to limit the present invention.

[0030] Unless otherwise stated, all experimental methods used in the following examples are conventional methods, and all materials, reagents, etc. used are commercially available products.

[0031] Example 1 MnSO4·H2O was used as the manganese source and FeSO4·7H2O was used as the iron source. The molar ratio of MnSO4·H2O to FeSO4·7H2O was 9:1, and the materials were solid-phase mixed. The homogeneously mixed materials were heated to 600°C for high-temperature solid-phase sintering to obtain the lithium manganese iron phosphate precursor (Mn 0.9 Fe 0.1 The reaction is as follows: 18MnSO4·H2O+2FeSO4·7H2O→10(Mn 0.9 Fe 0.1 )2O3+20SO2↑+32H2O↑+5O2↑

[0032] (M 0.9 Fe 0.1 )2O3, lithium carbonate, and ammonium dihydrogen phosphate were mixed in a solid state, ground in a sand mill, and sintered at high temperature at 500°C to obtain lithium manganese iron phosphate LiMn 0.9 Fe 0.1 PO4 was obtained. The reaction formula is as follows: 2(Mn 0.9 Fe 0.1 )2O3+2Li2CO3+4NH4H2PO4→4LiMn 0.9 Fe 0.1 PO4+2CO2↑+4NH3↑+6H2O↑+O2↑

[0033] In Figure 1, the thick black line indicates LiMn 0.9 Fe 0.1 PO4 precursor (Mn 0.9 Fe 0.1 1 is an X-ray diffraction (XRD) pattern of the (Mn)2O3. As can be seen from FIG. 1, the material synthesized in the embodiment of the present invention is0.983 Fe 0.017 )2O3 peak.

[0034] Figure 2 shows the (Mn 0.9 Fe 0.1 As can be seen from Figure 2, this material is a homogeneous material with good morphology. The particle size and tap density of the test material are D50 6μm and tap density 2.4g / cm 3 Therefore, what was synthesized in this example was not a simple mixture of manganese oxide and iron oxide, but manganese iron oxide.

[0035] Figure 3 shows lithium manganese iron phosphate LiMn 0.9 Fe 0.1 Scanning electron microscope (SEM) image of PO4 shows good morphology of the material. The particle size and tap density of the material were measured, and the D50 was 2μm and the tap density was 1.5g / cm 3 reached.

[0036] Example 2 MnSO4·H2O was used as the manganese source and FeSO4·7H2O was used as the iron source. The molar ratio of MnSO4·H2O to FeSO4·7H2O was set to 6:4. The materials were mixed in a solid state and the homogeneously mixed material was heated to 500°C for high-temperature solid-state sintering to obtain a lithium manganese iron phosphate precursor (Mn 0.6 Fe 0.4 The reaction is as follows: 12MnSO4·H2O+8FeSO4·7H2O→10(Mn 0.6 Fe 0.4 )2O3+20SO2↑+68H2O↑+5O2↑

[0037] (M 0.6 Fe 0.4 )2O3, lithium carbonate, and ammonium dihydrogen phosphate were mixed in a solid state, ground in a sand mill, and sintered at high temperature at 500°C to obtain lithium manganese iron phosphate LiMn 0.6 Fe 0.4 PO4 was obtained. The reaction formula is as follows: 2(Mn 0.6 Fe0.4 )2O3+2Li2CO3+4NH4H2PO4→4LiMn 0.6 Fe 0.4 PO4+2CO2↑+4NH3↑+6H2O↑+O2↑

[0038] Figure 4 shows lithium manganese iron phosphate LiMn 0.6 Fe 0.4 As can be seen from Figure 4, the morphology of the prepared lithium iron manganese phosphate material was good.

[0039] The particle size, specific surface area, and tap density of the material were measured, and the D50 of the material was 1.5 μm and the specific surface area was 15 m 2 / g, tap density is 1.3g / cm 3 and the compressed density of the material is 2.8 g / cm 3 This is the same as the general commercial product, which is 0.8 to 1.0 g / cm 3 and tap density of 2.3g / cm 3 It is much higher than the compression density of the general commercial product 20m 2 / g. The higher the compression density, the higher the roll compression density of the resulting electrode sheet, and the thinner the electrode sheet, the more electrode sheets can be accommodated in a given battery case, ultimately resulting in a battery with a higher energy density. The smaller the specific surface area, the lower the binder content and the higher the proportion of active material, further increasing the energy density of the battery. The smaller the specific surface area, the fewer side reactions between the material and the electrolyte, improving the battery's shelf life and cycle life.

[0040] Example 3 Spinel-type lithium manganese oxide LiMn2O4 and lithium manganese iron phosphate LiMn 0.6 Fe 0.4 The mixture with PO4 was used as the active material for the lithium-ion battery cathode sheet, where the lithium manganese spinel material accounted for 80% of the cathode active material and the lithium manganese iron phosphate material accounted for 20%.

[0041] The positive electrode active material was mixed with a conductive agent and a binder to prepare a positive electrode slurry. The solid content of the slurry was 97.2% active material, 1.7% conductive agent (conductive carbon black, conductive graphite, conductive carbon nanotubes, graphene), and 1.1% binder (polyvinylidene fluoride). The content of the solvent N-methylpyrrolidone was adjusted so that the slurry solid content was about 75%. The slurry was uniformly stirred and applied to the surface of a current collector aluminum foil, dried, roll pressed, and sliced ​​to obtain a positive electrode sheet.

[0042] The cylindrical full battery assembled with the above positive electrode sheet was tested for cycle performance at 0.5 C charge and 1 C discharge. The cylindrical battery was model R34235, with a diameter of 34 mm and a height of 235 mm.

[0043] Comparative Example 1 Spinel-type lithium manganese oxide LiMn2O4 and lithium manganese iron phosphate LiMn 0.6 Fe 0.4 The mixture with PO4 was used as the active material for the positive electrode sheet of a lithium-ion battery. For comparison, the lithium manganese spinel material accounted for 80% of the positive electrode active material, and the lithium manganese iron phosphate material accounted for 20%.

[0044] The above positive electrode active material was fabricated into a cylindrical full cell in the same manner as in Example 3.

[0045] As shown in Figure 5, when cycling was terminated at 70% decay, the battery assembled with the lithium manganese iron phosphate synthesized in Example 2 could be cycled 1100 times with an energy density of 140Wh / kg, whereas the battery assembled with the lithium manganese iron phosphate prepared by the conventional liquid phase method in Comparative Example 1 could be cycled 800 times with an energy density of 130Wh / kg. The improved cycle performance and energy density are mainly due to the high compaction density of the material.

[0046] The battery was left in a fully charged state at room temperature for 28 days, and the capacity before the storage was set to 100%. The remaining capacity ratio and charge / discharge recovery capacity ratio after storage can reflect the self-discharge of the battery and the side reaction between the material and the electrolyte. The "fully charged performance after storage at room temperature for 28 days" of the batteries obtained in Example 3 and Comparative Example 1 was measured. The results are shown in Table 2 below.

[0047] JPEG0007602031000002.jpg26170

[0048] As can be seen from Table 2, the battery of Comparative Example 1 has a remaining capacity ratio of 92.44% and a recovered capacity ratio of 96.35% after standing, while the battery of Example 3 has a remaining capacity ratio of 94.79% and a recovered capacity ratio of 98.05% after standing, both of which are superior to the battery of Comparative Example 1, indicating that there is less side reaction between the material synthesized in the present invention and the electrolyte. This is mainly due to the small specific surface area of ​​the material of the Example.

[0049] Example 4 Industrial grade MnSO4·H2O was used as the manganese source, which was ground to micron size using a sand mill, heated to 150℃ to cause the manganese sulfate to lose its water of crystallization, and then heated to 900℃ for thermal decomposition to produce the lithium manganese phosphate precursor Mn3O4. The overall reaction scheme is as follows: 3MnSO4·H2O→Mn3O4+3SO2↑+3H2O↑

[0050] Mn3O4, lithium carbonate, and ammonium dihydrogen phosphate were mixed in a solid state, crushed in a sand mill, and sintered in a high-temperature solid state at 600°C to obtain lithium manganese phosphate LiMnPO4. The reaction formula is as follows: 4Mn3O4+6Li2CO3+12NH4H2PO4→12LiMnPO4+6CO2↑+12NH3↑+12H2O↑+5O2↑

[0051] Example 5 After industrial grade FeSO4·7H2O is used as the iron source, it is ground to micron size in a sand mill and heated to 70-98℃. Iron sulfate (III) starts to lose water of crystallization and becomes FeSO4·4H2O. When it is further heated, it continues to lose water and becomes FeSO4·H2O at 86-159℃. Finally, it completely loses water of crystallization and becomes FeSO4 at 227-283℃. When it exceeds 300℃, FeSO4 starts to melt due to thermal decomposition. When it is further heated to 653-716℃, it thermally decomposes to produce the lithium iron phosphate precursor Fe2O3. The overall reaction equation is as follows: 4FeSO4·7H2O→2Fe2O3+4SO2↑+28H2O↑+O2↑

[0052] Fe2O3, lithium carbonate, and ammonium dihydrogen phosphate were mixed in a solid state, ground in a sand mill, and then sintered at high temperature at 700℃ to obtain lithium iron phosphate LiFePO4. The reaction formula is as follows: Fe2O3+Li2CO3+2NH4H2PO4→2LiFePO4+CO2↑+2NH3↑+2H2O↑+O2↑

[0053] Example 6 After industrial grade FeSO4·7H2O was used as the iron source and ground to micron size in a sand mill, iron sulfate(III) lost its water of crystallization when heated to 200℃, and decomposed at 1000℃ to produce the lithium manganese iron phosphate precursor Fe2O3. The overall reaction equation is as follows: 4FeSO4·7H2O→2Fe2O3+4SO2↑+28H2O↑+O2↑

[0054] Fe2O3, lithium carbonate, manganese dihydrogen phosphate, and Mn2O3 were mixed in a solid state, ground in a sand mill, and then sintered at high temperature at 700℃ to obtain lithium manganese iron phosphate LiFeMnPO4. The reaction formula is as follows: 2Mn2O3+8Fe2O3+20Li2CO3+20Mn(H2PO4)2·2H2O→40LiMn 0.6 Fe 0.4 PO4+20CO2↑+80H2O↑+5O2↑

[0055] Example 7 When industrial grade MnSO4·H2O was used as the manganese source and crushed to micron size in a sand mill, it was heated to 150℃, whereupon the manganese sulfate lost its water of crystallization, and when it was further heated to 900℃, it was thermally decomposed to produce the lithium manganese iron phosphate precursor Mn3O4. The overall reaction scheme is as follows: 3MnSO4·H2O→Mn3O4+3SO2↑+3H2O↑

[0056] Mn3O4, lithium carbonate, iron(III) phosphate, and ammonium dihydrogen phosphate are mixed in a solid state, ground in a sand mill, and sintered at high temperature at 600℃ to obtain lithium manganese iron phosphate LiMn 0.6 Fe 0.4 PO4 was obtained. The reaction formula is as follows: 6NH4H2PO4+2Mn3O4+5Li2CO3+4FePO4·2H2O→10LiMn 0.6 Fe 0.4 PO4+5CO2↑+17H2O↑+2O2↑+6NH3↑

[0057] The above embodiments are merely preferred embodiments given to fully explain the present invention, and the scope of protection of the present invention is not limited to these embodiments. Any equivalent replacement or conversion made by those skilled in the art based on the present invention is included within the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the scope of the claims.

Claims

1. A step S1 of solid-phase mixing a manganese source and an iron source to obtain a first mixture; The first mixture is solid-phase sintered at 300 to 1200° C. to obtain manganese iron oxide (Mn x Fe 1-x-y ) m O n Step S2 to obtain The manganese iron oxide (Mn x Fe 1-x-y ) m O n Step S3 of solid-phase mixing the lithium source and the phosphorus source to obtain a second mixture; The second mixture is solid-phase sintered at 350 to 900° C. to obtain lithium manganese iron phosphate LiMn x Fe 1-x-y P.O. 4 Step S4 to obtain wherein 0<x<1, 0<y<1, and x+y<1.

2. 2. The method for producing lithium manganese iron phosphate according to claim 1, wherein the manganese source is one or more of manganese sulfate, manganese carbonate, manganese acetate, manganese phosphate, manganese nitrate, manganese oxalate, and manganese citrate, each of which may or may not contain water of crystallization.

3. 2. The method for producing lithium manganese iron phosphate according to claim 1, wherein the iron source is one or more of iron sulfate (II), iron carbonate (II), iron acetate (II), iron phosphate (II), iron nitrate (II), iron oxalate (II), iron citrate (II), iron sulfate (III), iron carbonate (III), iron acetate (III), iron phosphate (III), iron nitrate (III), iron oxalate (III), and iron citrate (III), each of which may or may not contain water of crystallization.

4. 2. The method for producing lithium manganese iron phosphate according to claim 1, wherein the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium phosphate, lithium oxalate, lithium acetate, lithium sulfate, lithium nitrate, and lithium chloride.

5. 2. The method for producing lithium manganese iron phosphate according to claim 1, wherein the phosphorus source is one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium tripolyphosphate, phosphoric acid, calcium phosphate, phosphate ester, lithium dihydrogen phosphate, iron(III) phosphate, lithium phosphate, lithium dihydrogen phosphate, and manganese phosphate.

6. In steps S1 and S3, one or more of a carbon source, an M source, and an N source are further added during solid phase mixing; After the solid-phase sintering in steps S2 and S4, manganese iron oxide (Mn x Fe 1-x-y M y ) m O n N z / C and lithium manganese iron phosphate LiMn x Fe 1-x-y M y P.O. 4-z N z The method for producing lithium manganese iron phosphate according to claim 1, wherein the lithium manganese iron phosphate is obtained by the above-mentioned method. Here, the M source is a doping cation source, the N source is a doping anion source, and 0≦z≦0.1, 1:3.5≦m:(n+z)≦1:

1.

7. 7. The method for producing lithium manganese iron phosphate according to claim 6, wherein the carbon source is one or more of sucrose, glucose, fructose, citric acid, phenolic resin, polyvinyl alcohol, polyethylene glycol, starch, carbon black, acetylene black, graphite, graphene, and conductive carbon tubes.

8. 7. The method for producing lithium manganese iron phosphate according to claim 6, wherein the cation source includes one or more of aluminum, magnesium, nickel, cobalt, titanium, copper, calcium, niobium, chromium, zinc, lanthanum, antimony, tellurium, thoronium, tungsten, indium, and yttrium, and the anion source includes fluorine and / or sulfur.

Citation Information

Patent Citations

  • Preparation method of lithium iron manganese phosphate cathode composite material

    CN102738465A

  • Lithium iron manganese phosphate cathode material and preparation method and application thereof

    CN111933915A

  • Production of lithium-ion battery positive-material lithium manganate and its precursor manganese oxide

    CN1897333A